Hard question on global educational change, Policies, Practices and the future of education by Pasi Sahlberg, Jonathan Hasak, Vanessa Rodriguez and associates, Teachers College, Columbia University, 2017. - Arleta Suwalska (Studia z Teorii Wychowania)
The book is recommended as a coursebook for teachers, who seek for indispensable knowledge about hard questions on global educational change, unfolded from varied dimensions and from different countries. This impressive book consists of nine chapters. This book reveals pedagogical aspects due to the global changes in the current world and tries to present the perspective of a better way in education. The researchers should perceive the practical aspect of educational reforms and their practical dimensions in the varied educational systems.